2008
DOI: 10.1002/eji.200737792
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee CD4+ T cells are relatively insensitive to HIV‐1 envelope‐mediated inhibition of CD154 up‐regulation

Abstract: CD40-CD154 interaction forms a key event in regulation of crosstalk between dendritic cells and CD4 T cells. In human immunodeficiency virus (HIV)-1 infected patients CD154 expression is impaired, and the resulting loss of immune responsiveness by CD4+ T cells contributes to a progressive state of immunodeficiency in humans. Although chimpanzees are susceptible to chronic HIV-1/SIVcpz infection, they are relatively resistant to the onset of AIDS. This relative resistance is characterized by maintenance of CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the induction of CD154 is decreased in HIV-1-infected individuals and it is noteworthy that chimpanzees that are susceptible to chronic infection by HIV-1 but rarely develop subsequent immunodeficiency or disease progression, retain their ability to upregulate CD154 in the context of HIV[46]. In keeping with previous reports[47], we have found that cross-linking of CD4 with a monoclonal antibody to domain 1 also leads to inhibition of CD154 upregulation in response to pneumococcal antigens (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the induction of CD154 is decreased in HIV-1-infected individuals and it is noteworthy that chimpanzees that are susceptible to chronic infection by HIV-1 but rarely develop subsequent immunodeficiency or disease progression, retain their ability to upregulate CD154 in the context of HIV[46]. In keeping with previous reports[47], we have found that cross-linking of CD4 with a monoclonal antibody to domain 1 also leads to inhibition of CD154 upregulation in response to pneumococcal antigens (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…As with the HIV-1-infected chimpanzees, these two SIVcpz-infected chimpanzees seem to lack the profound changes to the immune system that are found in HIV-1-infected humans (Gougeon et al 1997 ;Rutjens et al 2008Rutjens et al , 2010. Given the apparent pathogenic outcome of SIVcpz infection of wild chimpanzees, it should be possible to identify, in these captive animals, disease mechanisms that are shared with HIV-1-infected humans.…”
Section: Examining the Virus-host Relationships Responsible For Genermentioning
confidence: 95%